3D Si/ITO/WO3 photoelectrode with a micropost array structure for photocatalysis enhancement. (20th October 2017) - Zheng, Deyin; Jiang, Xiufen; Liu, Mengyin; Zhao, Xin; Wang, Weichao; Sun, Guangyi
Abstract: In this paper, a three-dimensional (3D) tandem Si/ITO/WO3 photoelectrode system with a high-aspect-ratio (HAR) micropost array structure based on a 'Z-scheme' is designed to enhance photocatalytic performance. To produce such a photoelectrode system, microposts were first fabricated on a Si substrate by deep reactive ion etching (DRIE), followed by deposition of an indium tin oxide (ITO) layer and tungsten trioxide (WO3 ) layer on microposts. The photocatalytic performance was verified by the degradation of methylene blue (MB, C16 H18 ClN3 S) under visible light conditions. In the photocatalytic test, photoelectrode samples of a 0.5 cm 2 footprint were used to degrade 15 ml MB (10 mg l −1 ). Experimental results indicate that the 3D micropost WO3 /ITO/Si structure has a higher efficiency compared with the 2D planar WO3 /ITO/Si structure. A decrease of 83.6% in MB concentration within 30 min is observed in the preliminary degradation test. The HAR photoelectrode configuration can dramatically increase the surface-to-volume ratio, not only increasing the total incident light absorption efficiency, but also facilitating the oxidation–reduction reaction in the semiconductor-liquid interface.